Co-occurrence of acanthosis nigricans and bladder adenocarcinoma – case report - Olek-Hrab, Karolina; Silny, Wojciech; Żaba, Ryszard; Osmola-Mańkowska, Agnieszka; Mackiewicz-Wysocka, Małgorzata; Dańczak-Pazdrowska, Aleksandra (Contemporary Oncology/Współczesna Onkologia, 2013)
Acanthosis nigricans (AN) is characterized by the occurrence of symmetrical velvety hyperpigmented plaques that can be observed in each location on the skin. However, the lesions are most frequently located in the axillary, inguinal and nuchal areas. Primarily, the lesions appear as hyperpigmented focuses which later transform into papillary lesions. There are two forms of the disease – benign and malignant. Malignant AN is considered to represent paraneoplastic syndrome co-occurring with advanced cancer, but as such it is not malignant. This article presents a case of a patient diagnosed with AN and coexisting bladder cancer and discusses the case in the context of available literature.